Measurement of the cosmic ray spectrum above 4×10^18 eV using inclined events detected with the Pierre Auger Observatory - Dova, María Teresa (2014)
A measurement of the cosmic-ray spectrum for energies exceeding 4×1018 eVis presented, which is based on the analysis of showers with zenith angles greater than60◦ detected with the Pierre Auger Observatory between 1 January 2004 and 31 December 2013. The measured spectrum confirms a flux suppression at the highest energies.Above 5.3×1018 eV, the ?ankle?, the flux can be described by a power law E −γ with index γ = 2.70 ± 0.02 (stat) ± 0.1 (sys) followed by a smooth suppression region. For the energy(Es ) at which the spectral flux has fallen to one-half of its extrapolated value in the absence of suppression, we find Es = (5.12 ± 0.25 (stat)−1.2 (sys))×10 eV.